2020
DOI: 10.3390/jcm9124068
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiome Signatures in Hematological Cancers Reveal Predominance of Actinomyces and Rothia Species

Abstract: The endogenous microbiome of healthy individuals in oral cavities is diverse, representing over 700 bacterial species. Imbalance in oral and gut microbiome composition and associated gene expression has been linked to different forms of hematological (blood) cancers. Our objective is to compare oral microbiome profiles of patients with blood cancers (BC group: N = 39 patients, n = 124 oral samples) to those of healthy control subjects (HC group: N = 27 subjects, n = 100 oral samples). Saliva samples and swabs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, which host factor causes Actinomyces colonization in breast cancer patients needs to be further explored. Studies have shown that Actinomyces could invade damaged mucosa with reduced mucosal protection (Clarridge 3rd & Zhang, 2002; Mougeot et al, 2020). Malignancy‐like symptoms caused by Actinomyces have been reported previously (Roh et al, 2019; Savoca et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, which host factor causes Actinomyces colonization in breast cancer patients needs to be further explored. Studies have shown that Actinomyces could invade damaged mucosa with reduced mucosal protection (Clarridge 3rd & Zhang, 2002; Mougeot et al, 2020). Malignancy‐like symptoms caused by Actinomyces have been reported previously (Roh et al, 2019; Savoca et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…PERMANOVA analyses were performed using a mixed model with unrestricted permutation of raw data, 9,999 permutations, and type III partial sum of squares ( Clarke and Gorley, 2006 ), as previously implemented ( Mougeot et al, 2019 , 2020 ). Fixed factors were “Diagnosis” (e.g., HNC vs. HC) and “Sample site” (B, P, S, and T).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, without implying a causal effect, a link between oral microbiome dysbiosis and cancer has been suggested by several studies ( Kudo et al, 2016 ; Hayes et al, 2018 ; Mohammed et al, 2018 ; Wu et al, 2018 ; Mougeot et al, 2020 ). For instance, Fusobacterium nucleatum was found overabundant in the oral cavity of patients with colon cancer and lymph node metastasis ( Kudo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to analyze (1) the oral microbial community and potential changes to the community pattern upon chemotherapy in breast cancer patients and (2) a potential role of Actinomyces ssp. during the course of therapy as a suspected pathogen for the development of oral diseases ( 26 ). We suggest that chemotherapy in general changes the oral microbiome as already demonstrated and reviewed for the gut microbiome ( 27 ).…”
Section: Introductionmentioning
confidence: 99%